Re-examining the Urban Civilization using the Minimum Wage Level as an Alternative Value-evaluation Basis. (2017) - Weng, Yu-Chi
Abstract: In recent decades, as the rapid economic development proceeds worldwide, more and more regions are making attempts to increase the growth level mainly considering the mainstream economic indicators, e.g., per capita income or gross domestic production (GDP). Nevertheless, as the environmental economists from the perspective of environmental Kuznets curve argued, the aforementioned economic indicators would omit the real value of the human life quality and the environmental/ecological systems. Therefore, a large body of literature are trying to establish integrated indicator systems to diagnose the current civilization progresses, e.g., the Kuznets curve and sustainability indicators. Although a variety of adjustments have been made to diagnose the current civilization, e.g., the Purchasing Power Parity (PPP), the data of PPP is of highly uncertainty. Instead of PPP, this study makes an attempt to utilize the minimum wage level as a conversion basis to adjust the mainstream economic indicator. The ratios among economic indicators and an environmental indicator, the per capita municipal solid waste (MSW) collection representing the civilization progresses are diagnosed and compared in several megacities in East Asia, including Tokyo, Osaka, Seoul, Beijing, Shanghai, Guangzhou, Taipei and Hong Kong. Based on the results, the current mainstream value of civilization can be re-examined from an alternative perspective and concrete proposals can be made toward real sustainable development.